Effects of extremely low frequency electromagnetic field on physical and biochemical characteristics of selected tissue cultured plants - Riry Prihatini (2014)
The extremely low frequency electromagnetic field (ELF-EMF) occurs naturally from the Earth and artificially from human inventions. The electric power lines which lie across many plantations in Malaysia is one of the examples of the source of ELF-EMF. Earlier research demonstrated that some plants exposed to ELF-EMF respond positively in terms of growth and biochemical properties. Therefore, it was hypothesized that ELF-EMF is able to stimulate plant’s growth. The objectives of this study were to develop a suitable ELF-EMF generator, to determine the effects of ELFEMF on plant development, and to analyze the biochemical changes occurs in plants exposed to ELF-EMF. Initially, an ELF-EMF generator, the coGEM 1000 was constructed using four coils of copper wires that were connected to a transformer, a multimeter, and a rheostat. The coGEM 1000 suitable for tissue culture plants is able to produce stable and uniform 6 and 12 mT 50 Hz ELF-EMF in the four coils of the ELF-EMF generator. Four different species of tissue culture plants, namely tobacco plant, banana, orchid, and ficus were exposed to ELF-EMF. All these in vitro plantlets were incubated in a controlled environment prior to exposure to 6 and 12 mT of 50 Hz ELF-EMF for a period of 0.5, 1, 2, and 4 hours. The parameters observed were the number of shoots, shoot height, and number of leaves (growth characteristics) and biochemical properties, such as chlorophyll a and b content, total chlorophyll content, ratio chlorophyll a/b, carotene content, and activities of the enzymes namely catalase (CAT), ascorbate peroxidase (APX), superoxide dismutase (SOD), and glutathione reductase (GR). For tobacco plant, the exposure to 6 mT ELF-EMF for an hour had increased the shoot height (3 cm),chlorophyll a (32.8 mg/g) and SOD activity (1.9 U/mg protein); whereas,the exposure to 6 mT ELF-EMF for 0.5 hour had increased the number of shoots (1.4) and total soluble proteins (23.3 mg/g) of the banana plant. However for orchid plants, higher ELF-EMF the exposure to (12 mT) for longer duration (4 hours) had induced a high number of shoots (3.5),number of leaves (10.2) and CAT enzyme activity (1.0 U/mg protein). In contrast to the former, ficus plant exposed to extended periode of ELFEMF did not induce any changes in the growth characteristics. However;the exposure of ficus plant to 12 mT ELF-EMF for 4 hours showed an increased in the activity of CAT (9.8 U/mg protein) and APX (13.2 U/mg protein). It is concluded that different plant species requires different strength and duration of exposure to ELF-EMF to promote growth and development. In addition, the exposures of the selected plant species to the ELF-EMF were able to promote the plant abilities to resist the presence of reactive oxygen species (ROS) generated in tissue culture. These have been illustrated by the increase of the various antioxidative enzymes activities (SOD, CAT and APX) presence in the selected plants species (viz. tobacco, orchid, and ficus plant, respectively). These results suggest that the application of ELF-EMF may help to promote in vitro plant growth through creating a plant that can resist the ROS. This findings provide a foundation for further apllication of the ELF-EMF in promoting plant growth.